Paediatric Primary Testicular Follicular Lymphoma : A Diagnostic Challenge - Aysha Suhana; Anand Vijaya Narayanan; Sangeetha Keloth Nayanar; Jithin TK; Gopakumar KG (Online Journal of Health & Allied Sciences)
Primary testicular follicular lymphoma (PTFL) is a unique extra-nodal variant of follicular lymphoma. It is commonly seen in children and young adults. They lack evidence of the BCL2 translocation, thus biologically differ from nodal follicular lymphoma. This report presents a case of PTFL in a 5-year-old boy characterizing, the clinical presentation and pathological features. The true incidence of PTFL is unknown owing to its rarity; nevertheless, about 25 cases have been reported in the literature so far. This would be one among the few cases reported worldwide of primary follicular lymphoma of the testis.